Pump‐Probe Imaging of Ultrafast Laser Percussion Drilling of Glass in Single Pulse, MHz‐ and GHz‐Burst Regimes - Pierre Balage; Théo Guilberteau; Manon Lafargue; Guillaume Bonamis; Clemens Hönninger; John Lopez; Inka Manek‐Hönninger (Advanced Materials Interfaces)
Abstract A pump‐probe shadowgraphy study of femtosecond laser percussion drilling on glass samples is reported applying three different operating regimes, which are the standard repetitive single pulse, the MHz‐ and the GHz‐burst modes. The comparison of pump‐probe imaging in the MHz‐burst and the GHz‐burst regimes is demonstrated for the first time to the best of knowledge. Synchronizing a single pulse probe with a pump operating in a burst regime constitutes a real novelty in femtosecond laser micromachining studies. By this means, a better understanding of the drilling process dynamics of the two burst regimes is provided and reveals the differences between these regimes. Especially, the process of through via drillings of different hole depths in the GHz‐burst regime is investigated in sodalime glass. The results of the pump‐probe shadowgraphy show that the ablation plume in the GHz‐burst regime has an essential role in the drilling process as it stops as soon as the plume escapes from the through hole explaining the final hole morphology observed for deep through via drillings.